2005
DOI: 10.1128/jcm.43.3.1433-1436.2005
|View full text |Cite
|
Sign up to set email alerts
|

Survey of emm -Like Gene Sequences from Pharyngeal Isolates of Group C and Group G Streptococci Collected in Spain

Abstract: We conducted a nationwide surveillance of the variable 5 emm-like (M-like protein gene) sequences from 214 pharyngeal group C and group G streptococci. Almost 75% of the isolates exhibited emm or emm-like sequences previously described. We identified six new 5 emm-like regions, and almost 23% of the isolates were nontypeable. Five emm-like sequences accounted for more than 50% of the isolates in group C and group G, suggesting horizontal gene transfer between strains of different species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
9
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
2
9
1
Order By: Relevance
“…It is noted that stC839.0 was reported to be a dominant emm type from group C S. dysgalactiae subsp. equisimilis isolates in Spain and Australia (2,12). In our study, this type was also found in some (11.7%, 32/274) group G S. dysgalactiae subsp.…”
supporting
confidence: 51%
“…It is noted that stC839.0 was reported to be a dominant emm type from group C S. dysgalactiae subsp. equisimilis isolates in Spain and Australia (2,12). In our study, this type was also found in some (11.7%, 32/274) group G S. dysgalactiae subsp.…”
supporting
confidence: 51%
“…A previous study in Thailand showed the predominant M protein type of GAS to be M93 (20.75z); other M types included M1, M44/61, and M25 (17). The M protein gene (emm and emmL) prevalence in GCS/GGS found in our study was higher than the 76.63z found in Spain (13). Of the blood-isolated GAS, GCS, and GGS, 90.0z, 84.6z, and 78.3z, respectively, had the M protein.…”
contrasting
confidence: 50%
“…Although > 200 emm types of GAS (15) and >60 emm types of GCS/GGS (7) have been reported, but the important types associated with invasive infection are unclear (7). M-like proteins may benefit GCS and GGS colonizing in the pharynx (13). The high diversity of the emm and emmL genes facilitates emm typing (13), and presents an alternative to serological typing, which has limitations that include nontypeable M proteins, specific antisera that are difficult to produce, and the potential for missing novel M-types.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical manifestations included shock, hepatic insufficiency, renal failure, disseminated intravascular coagulation, erythematous rash, and soft-tissue necrosis. It has been suggested that the horizontal transfer of the emm sequences and the following recombination events occur among beta-hemolytic streptococci such as GAS, GCS, and GGS (1,24,25). Such a mechanism could be responsible for the development of gene mosaics and the evolution of the emm genes in beta-hemolytic streptococci (29).…”
mentioning
confidence: 99%